Policy & progress: 1955-56 - The British Productivity Council (London: The British Productivity Council, 1956)
The anti-inflation measures have not left productivity unaffected; though still 60 per cent. Above pre-war average it is not high enough to sustain our needs. Success of the council's activities is largely attributed to voluntary work unsparingly given by LPC members and must depend on its expansion. The Council believes in the closest co-operation and understanding between both sides of industry and in the widest diffusion of the existing technical knowledge and experience. To these ends over one hundred Local Productivity Committees and Associations, with joint membership, have been set up in the main industrial areas.
Keywords: Policy Making -- Administrative Report